Identification and antimicrobial susceptibility of bacteria and yeasts isolated from healthy dogs and dogs with otitis externa - Lyskova, P; Vydrzalova, M; Mazurova, J (Journal of veterinary medicine. A, Physiology, pathology, clinical medicine, 2007)
The bacterial and fungal flora of the external ear canal of dogs with otitis externa and of healthy dogs were studied. The most frequently isolated microorganism from otitic ears was Staphylococcus intermedius (58.8%), followed by Malassezia pachydermatis (30.9%), Streptococcus canis (29.9%), Proteus spp. (14.4%) and Escherichia coli (10.3%). A statistical analysis of our results showed that the prevalence of these microorganisms is significant in dogs with otitis externa. Furthermore, the antimicrobial susceptibility patterns of isolated strains were determined. Majority of all bacterial isolates were most susceptible to gentamicin. Malassezia pachydermatis, the most prevalent yeast in this study, showed an excellent level of susceptibility to all antifungal agents tested.
Keywords: Drug Resistance, Fungal; Male; Treatment Outcome; Streptococcus; Dose-Response Relationship, Drug; Animals; Drug Resistance, Bacterial; vztah mezi dávkou a účinkem léčiva; psi; mužské pohlaví; Female; Malassezia; otitis externa; Ear; fungální léková rezistence; ženské pohlaví; Microbial Sensitivity Tests; Dog Diseases; Anti-Bacterial Agents; zvířata; Otitis Externa; nemoci psů; ucho; Dogs; bakteriální léková rezistence; Staphylococcus; mikrobiální testy citlivosti; antibakteriální látky; výsledek terapie